Constitutional amendment in Canada - Macfarlane, Emmett (University of Toronto Press, 2016)
"In Canada, the 1982 Constitution Act contains the amending formula, which outlines a set of procedures required to make changes to the constitution. Recent debates over Senate reform, the status of the Supreme Court of Canada, and the rules governing royal succession have highlighted how important the amending formula is in maintaining the vitality and relevance of the governing system."--